Lithium-ion Battery Charging System using Constant-Current Method with Fuzzy Logic Based ATmega16 - Rossi Passarella; Ahmad Fali Oklilas; Tarida Mathilda (Institute of Advanced Engineering and Science, 2014)
In this charging system, constant-current charging technique keeps the current flow into the battery on its maximum range of 2A. The use of fuzzy logic control of this charging system is to control the value of PWM. PWM is controlling the value of current flowing to the battery during the charging process. The current value into the battery depends on the value of battery voltage and also its temperature. The cutoff system will occur if the temperature of the battery reaches its maximum range.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.5924